1974
DOI: 10.1002/eji.1830040914
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylcholine‐bearing components in homogenates of nematodes

Abstract: et d'l mmunologie, Thiverval-GrignonHomogenates prepared from the developmental stages of the nematodes, Nippostrongylus brasiliensis (a rat parasite) and Haemochus contortus (a sheep parasite) were found to react specifically with two myeloma sera that possess anti-phosphorylcholine binding activity. Some properties of the phosphorylbearing components and of the precipitation reaction are presented and the postulated biochemical nature of these components is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 10 publications
1
34
0
Order By: Relevance
“…A major post-translational modification of parasitic helminth antigens is apparently PC. This antigenic determinant has been detected in nematodes (5,8,34,35), in trematodes, including Schistosoma mansoni (9), and in the cestode Bothriocephalus scorpii (36). In fact, the frequency of serological cross-reactivity between cestodes, trematodes and, in particular, nematodes (37) may be accounted for by the broad distribution of PCbearing molecules.…”
Section: Discussionmentioning
confidence: 99%
“…A major post-translational modification of parasitic helminth antigens is apparently PC. This antigenic determinant has been detected in nematodes (5,8,34,35), in trematodes, including Schistosoma mansoni (9), and in the cestode Bothriocephalus scorpii (36). In fact, the frequency of serological cross-reactivity between cestodes, trematodes and, in particular, nematodes (37) may be accounted for by the broad distribution of PCbearing molecules.…”
Section: Discussionmentioning
confidence: 99%
“…PC is a widely distributed hapten that reacts with C-reactive protein -an acute phase protein which appears in serum during certain infections, inflammatory conditions and tissue damage (Anderson & McCarty, 1950). PC-like determinants have been found in bacteria (Brundish & Baddiley, 1968), parasites (Pery et al, 1974) and in fungi such as the dermatophytes E.Jloccosum and T. rnentagrophytes as well as Aspergillus fumigatus (Pepys & Longbottom, 1971). The PC-like component of E. joccosurn and A .…”
Section: Discussionmentioning
confidence: 99%
“…In our accompanying paper (Calderon & Shennan, 1987) the results indicated that the hapten PC, a structural component of dermatophytes (Baldo et al, 1977), appeared to be a dominant antigen during dermatophyte infections in mice. The hapten PC, found also in bacteria (Brundish & Baddiley, 1968) and parasites (Pery et al, 1974), binds to the acute phase C-reactive protein and the resulting complex is known to elicit some immunological reactions (Kaplan & Volanakis, 1974).…”
Section: Discussionmentioning
confidence: 99%